Peningkatan Kemandirian Lansia dalam Manajemen Penyakit Kronis Melalui Edukasi Partisipatif di Kelurahan Kuin Cerucuk - Alessandra Dielfiony Sipayung; Era Indrian; Fransiska Natasha Fardi; Norwita Dwi Priyono; Stefani Stefani; Yosafat Eliahkim Selan; Yunia Angela M; Sumiati Hartati; Maria Frani Ayu Andari Dias (JURNAL SUAKA INSAN MENGABDI (JSIM), 2026)
Elderly individuals in Kuin Cerucuk are susceptible to chronic diseases, particularly hypertension and diabetes mellitus, which are exacerbated by suboptimal health management and cultural dietary habits. This community service aimed to improve elderly independence in chronic disease management through a participatory education program. The implementation method involved a community-based approach consisting of three stages: assessment, educational intervention, and evaluation. The program utilized "Lansia Beriman" (Healthy Body, Devout Worship) interactive sessions, demonstrating local Banjar diet modifications, non-pharmacological pain management (warm compresses and deep breathing exercises), and family empowerment as medication supervisors. The results showed a significant increase in health literacy, with 100% of the elderly demonstrating improved understanding of medication adherence and diet control. Furthermore, elderly participants successfully mastered independent pain management techniques, reducing their reliance on chemical analgesics. Family involvement as medication supervisors effectively ensured therapy continuity. In conclusion, the participatory education approach, integrated with cultural values, significantly enhanced the independence and functional quality of life of the elderly in Kuin Cerucuk. Continuous periodic monitoring by community health centers is recommended to sustain these health improvements.